Future Directions for Conservation. (1st August 2016) - Keulartz, Jozef
Abstract : The use of target baselines or reference states for conservation and restoration has become increasingly problematic and impractical, due to rapid environmental change, the paradigm shift in ecology from a static to a dynamic view of nature, and growing awareness of the role of cultural traditions in the reconstruction of baselines. The various responses to this crisis of baselines will to a significant extent determine the future direction of nature conservation. Although some hold onto traditional baselines and others try to refine or redefine the reference concept, the debate is currently dominated by two widely diverging reactions to the crisis: while the so-called 'new environmentalists' or 'new conservationists' declare the whole baseline notion obsolete, replacing a backward-looking approach with a forward-looking one, the 're-wilders' push the baseline back to a deeper, more distant past. This article provides a critical assessment of the debate on these conversation options, with a special focus on the differences between Old World and New World perspectives.